Unraveling bioactive constituents isolated from knema hookeriana warb. As potential acetylcholinesterase inhibitors - Salihu, Abubakar Siddiq; Wan Salleh, Wan Mohd Nuzul Hakimi; Ab Ghani, Nurunajah; Arzmi, Mohd Hafiz; Sungthong, Bunleu; Kapavarapu, Ravikumar (LIDSEN Publishing Inc., 2025)
The Myristicaceae family, particularly the Knema genus, is renowned for its diverse bioactive compounds, including lignans, flavonoids, and phenolics. This study explores the phytochemical profile of Knema hookeriana Warb. leaves and evaluates their potential as acetylcholinesterase (AChE) inhibitors. Phytochemical extraction was performed using a cold maceration method with a polarity-gradient solvent system (hexane, ethyl acetate, and methanol). The isolated compounds were purified through chromatographic techniques and structurally characterized using spectroscopic analyses (IR, NMR, and MS) alongside literature comparison. AChE inhibitory activity was assessed using the Ellman method. Seven bioactive compounds were successfully isolated: aptosimon (1), cubebin acetate (2), bicubebin A (3), 5,7-dimethoxyflavone (4), 4',5,7-trimethoxyflavone (5), luteolin (6), and epicatechin (7). Among these, aptosimon (1) exhibited the most potent AChE inhibition, with an IC50 value of 60.8 µg/mL. Molecular docking studies corroborated the in vitro results, demonstrating strong AChE binding affinities for the compounds, with aptosimon (1) showing favorable interactions. These findings highlight the therapeutic potential of Knema species and their bioactive compounds, paving the way for further research into their nutraceutical and pharmaceutical applications, particularly in neurodegenerative disease management